The Analysis of Problem Solving Ability Viewed from Intuition in Integral Calculus Course - Eko Andy Purnomo; Yohanes Leonardus Sukestiyarno; Iwan Junaedi; Arief Agoestanto (International Conference on Science, Education, and Technology, 2022)
Students need to engage in analytical and logical thought processes, as well as the construction of mathematical knowledge and ideas, to solve problems. What these students are doing is an example of intuitive cognition. From what we can tell, many students, especially those taking Integral Calculus, do not fully use their mental capacities when attempting to solve issues. This research aimed to identify the extent to which intuition is used to solve problems encountered in the study of Integral Calculus. The method of this research was a descriptive qualitative method. A total of 43 participants from the FMIPA UNIMUS Mathematics Education Study Program participated in the study. The study's findings were that the problems persisted regardless of whether the children were high, middle, or poor achievers. The instruments used in this study are the evaluation questions, the intuition surveys, and the interviewing procedures for both the problem solver and the intuitive. They used evaluation tests, observations, and in-depth interviews to triangulate their results. Data analysis entails three stages: data reduction, display, and verification. Affirmatory intuition was most common among students with high problem-solving abilities. In contrast, those with average skills utilized a mix of Affirmatory and Anticipatory intuition. On the other hand, students with limited talents relied on Anticipatory intuition rather than actual intuition. The findings suggest that when presented with a problem, pupils' first instincts are not universal. It indicates that further investigation would develop pupils' innate ability to solve problems creatively.